Kajian Ilmiah Sifat Fungsional dan Pemanfaatan Rumput Laut Coklat Sargassum sp. Dibidang Pangan - Husnita Komalasari; Ine Karni (Jurnal Teknologi dan Mutu Pangan, 2023)
Sargassum sp. is a seaweed that belongs to the brown seaweed which is commonly found in Indonesian. This seaweed can be utilized in various industrial fields including in the food and health sectors. This study aims to determine the functional properties and utilization of Sargassum sp. in the food sector. The method of this research is literature studies from various sources such as Google Scholar, Science Direct, Pubmed and Research Gate and other. The selection of cited literature has gone through a screening process based on inclusion, special and exclusion criteria. In the health sector, Sargassum sp. has been widely used because of the content of functional compounds including alkaloids, phenolics, pigments, steroids and terpenoids, as well as fucosterols. These functional compounds have various health benefits such as antibiotics, anti-inflammatories, anti-obesity, anti-cancer, antioxidants, as well as lowering cholesterol, blood sugar and blood pressure. Meanwhile, in the food sector, Sargassum sp. can be used as a stabilizer, emulsifier, thickening and gelling agent. This is because Sargassum sp. has alginate content of 20-27%. Alginate is a polymer compound that is colloidal, forms a gel and is hydrophilic. Alginate is also known to have the ability to bind to polyvalent compounds which have better viscosity with better gel strength. Based on the literature review data that has been carried out, it is known that Sargassum sp. has a wide range of functional compound content that is beneficial to health and has various benefits in the food sector.